KELIMPAHAN JENIS VEGETASI HUTAN SEKUNDER BEKAS KEBAKARAN DI DESA KAMAL KABUPATEN SERAM BAGIAN BARAT - Yulianus D. Komul; Jopie Christian Hitipeuw (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2022)
The forest area of ​​Kamal village is included in secondary forest with convertible production forest land cover. The study was carried out in July – August 2020 using a combination of the strip method and the plotted line method to calculate the overall stand based on the growth rate in an area of ​​10,000 m2 with the condition of vegetation having succession due to forest fires in 1992 causing low biodiversity characterized by the dominance of species – types of secondary forest vegetation. Vegetation analysis results obtained 47 tree species with 29 families occupying all growth stages with the highest dominance controlled by species; marong merah (Commersonia bartramia), damar hitam (Canarium asperum Benth), red wood (Eugenia sp), kayu kikir (Eugenia sp) and pala hutan (Myrestica sp). Species Diversity Index (H') for tree level is 1.44% dominated by damar hitam (Canarium asperum .Benth), pole H' value is 1.16% dominated by Kenanga (Cananga odorata .Hook), Sapihan H' value was 1.13% dominated by damar hitam species (Canarium asperum Benth) while the Seedling rate H' value was 0.93% and dominated by damar hitam species (Canarium asperum .Benth). Based on the value of H' from various levels of growth, the diversity of wood forest products was categorized for the secondary forest research location after the fire in Kamal village was in the medium category with the condition of the species in each type of vegetation that was found to have developed and could survive for increased sustainability